ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Kasus Pada Perusahaan Manufaktur Sektor Industri Kosmetik) - Elly Lestari (Jurnal Ekonomi dan Manajemen, 2016)
The financial statements of a company is needed because the financial statements are expected to provide information to assess the development of the company. The purpose of this study was to analyze financial performance of the companies listed on the Indonesia Stock Exchange (Case Study on Cosmetic Industry Sector Manufacturing Company) in terms of financial ratio analysis. The research method used by the writer is descriptive research by analyzing financial statements using quantitative data and data analysis techniques used by researchers is the financial ratio is the liquidity ratio, solvency ratio and profitability ratio. Based on the liquidity ratio indicates that the company's current assets are very good so the company can meet the short-term debt in a timely manner, so that the state of the company are categorized in a liquid state. Of the solvency ratio shows that the company's assets is sufficient to secure the loan granted by creditors so that the state of the company is said to be in a state of solvability. The calculation of the profitability ratio showed poor state of the company. This is due to the intense competition with the emergence of new cosmetic products in the market. It should be held redesign in order to increase sales activities by maximizing the marketing and/orincrease the value of the product produced so as to attract more consumers. Companies should maintain management costs in order to remain careful and efficient, thus the company's ability to improve profitability in the future will be better.